Safety consideration of nutraceutical products in Malaysia: issues and concerns - Ismail, Suzi Fadhilah; Abdul Ghani Azmi, Ida Madieha; Daud, Mahyuddin; Safuan, Sahida (Lexis-Nexis, 2020)
Nutraceutical products have become widespread phenomenon for proclaimed benefits they seem to offer. Defining what products are classified as nutraceutical has always been a challenging task in some jurisdictions especially in Malaysia. Legally speaking, they cannot be considered as mere food, and they are not pharmaceutical drugs either. Due to uncertainty in its categorisation, nutraceutical manufacturers have taken advantage in producing and marketing those products to consumers. They have been making numerous health claims that were not based on clinical evidence as there is no legal requirement for such. Although some consumers might have benefited from the products, established research suggested that consumers are exposed to health issues and risks from a long-term consumption. By using qualitative method, this paper aims to examine regulatory issues and challenges encountered by the National Pharmaceutical Regulatory Authority (NPRA) and the Food Safety and Quality Division (FSQD) under the Ministry of Health Malaysia in regulating nutraceutical products. It is found that self-regulation as being in practice at present has to some extent, placed the nutraceutical industry in a very complacent position, and thus, putting consumers’ safety at stake. The paper concludes by proposing that for local atmosphere, governmental intervention via a stricter regulation and enforcement is required to ensure safer consumption of nutraceutical products — so that consumers may truly benefit from them.